Stratigraphic and sedimentary evidences for development of Aptian intrashelf basin in the structural Zagros zone, northern Fars Platform - Neda Khoshfam; Hossein Rahim Pour Bonab; Davood Jahani; Davood Morsalnejad (Journal of Stratigraphy and Sedimentology Researches, 2016)
Introduction The Cretaceous successions of the Arabian plate host main hydrocarbon reserves of the world and the Middle East. The Arabian plate had experienced particular sedimentary circumstances in the early Cretaceous so that the shape of sedimentary basin had drastically changed by salt diapirs movements and basement tectonics. However, these conditions caused creation and development of intrashelf basins in this time interval. The two main and well-known intrashelf basins are Bob basin and Kazhdumi basin which are respectively located in the northeast and the east of the Arabian plate. This study has focused on the Aptian sediments which are known by the term "Dariyan Formation" in the northern of the Persian Gulf. The study outlines the extension of the Aptian intrashelf basin in northern Fars platform within the structural Zagros zone. Material and Methods The Dariyan Formation was studied in detail by using thin sections which are prepared from cores and cuttings of two wells (Sarvestan and Ahmadi wells) in the northern Fars area. In addition data from a neighbor well (Qutbabad) are used to complete the data set for the study. Petrographic studies were carried out on more than 300 thin sections using Dunham classification. Various microfacies and facies sets are determined based on grain and texture content, energy index and other sedimentary factors in comparing recent and ancient environments. A southeast-northwest transect (AA' transect) was selected in order for better investigation of lateral facies and environmental changes in the studied area during the Aptian. Discussion of Results and Conclusions Facies analysis led to the identification of 8 microfacies into 4 facies sets: lagoon, shoal, open marine and basin facies sets. In the stratigraphic studies of the Dariyan Formation, three biozones (16, 17 and 18) are common which are introduced by Wynd 1965. Changes in fossil content of the Dariyan Formation mostly help to identify these biozones. In the lower parts of the Dariyan Formation, presence of Palorbitolina (early Aptian) in companied with Hensonella and Lithocodium aggregatum are marker of biozone 16 while in the upper Dariyan Formation, presence of Mesorbitolina (late Aptian) with conical Orbitolina and other small benthic foraminifera are sign of biozone 18. Biozone 17 could be identified by presence of pelagic fauna such as Globigerina. The Dariyan Formation is divided into two parts in the Ahmadi well and three parts in the Sarvestan well. In the Ahmadi well, sediments of the rock unit 1 belong to biozone 16 which starts by open marine mudstone to wackestone facies and continues by thick layered alternations of Orbitolina Hensonella wackestone, bioclast mudstone and bioclast pelloid wackestone/packstone facies. The rock unit 2 (biozone 18) includes Orbitolina bioclast pelloid grainstone (lagoon facies) in alternation of open marine wackestone/ mudstone. In the Sarvestan well, the lower Dariyan Formation is composed of sediments which belong to biozone 16. These sediments are just like the rock unit 1 in the Ahmadi well which include lagoonal microfacies set and they suddenly change to deep pelagic facies (biozone 17) of the middle Dariyan Formation. In the Sarvestan well, the upper Dariyan Formation is just like rock unit 2 in the Ahmadi well. It is composed of sediments belonging to biozone 18. Paleontological data from Iranian National Oil Company are representative of the presence and extension of biozone 17 towards the Kolah Qazi mountain. This pelagic set disappears towards the Qutbabad well (southeast of the studied area). Considering to low frequency of shallow high energy facies such as grain dominated grainstone and packstone facies besides lack of reefs and reefal biota, turbidities, and sedimentary structures such as slides, slumps and debris flows, there are not enough evidences to attribute a rimed carbonate shelf environment for the Dariyan Formation. In contrast regarding to lateral facies changes in the north Fars area and sudden changes of shallow facies sets into pelagic facies sets, it seems a homoclinal carbonate ramp to intrashelf basin could be the best model for the Dariyan formation in the studied area. The term “Sarvestan intrashelf” is proposed for this basin. Extension of the Sarvestan intrashelf can be defined by tracing changes in the lateral facies of the Dariyan Formation. Therefore despite previous visions, the Fars platform was not a monolith shallow platform. In addition, except Kazhdumi intrashelf basin, there were other deep and local intrashelf basins which were developed within the Fars platform.